Neuro-protective potential of quercetin during chlorpyrifos induced neurotoxicity in rats. (4th March 2019) - Kaur, Simranjeet; Singla, Neha; Dhawan, D. K.
Abstract: Chlorpyrifos (CPF) has been considered as one of the most potent organophosphates and is linked to several neurological disorders. On the other hand, Quercetin is a vital plant flavanoid and has been reported to regulate a number of physiological processes in the central nervous system. The present study was conducted to investigate the protective potential of quercetin during chlorpyrifos induced neurotoxicity. Female Wistar rats weighing 150–200 g were divided into four different groups viz: Normal control, CPF treated (13.5 mg/kg.b.wt. every alternate day), Quercetin treated (50 mg/kg.b.wt./day) and combined CPF and quercetin-treated. All the treatments were carried out for a total duration of eight weeks. Chlorpyrifos treatment showed significant alterations in the cognitive behavior and motor activities of rats, which were appreciably improved upon simultaneous supplementation with quercetin. Further, CPF treatment caused a significant inhibition in the enzyme activities of acetylcholinesterase and choline acetyltransferase, but caused an increase in the levels of acetylcholine in the brain. Further, chlorpyrifos exposure significantly elevated the levels of lipid peroxidation and protein carbonyl contents as well as the activities of catalase, superoxide dismutase, which were interestingly found to be decreased following co-treatment with quercetin. In contrast, CPF treatment decreased the activities of glutathione reductase, transferase, as well as levels of reduced and total glutathione in both the cerebrum and cerebellum but co-administration of quercetin, increased these levels. Chlorpyrifos treatment altered the neuro-histoarchitecture, which showed improvement upon quercetin supplementation. Hence, this study suggests that quercetin can be used as a prophylactic intervention to prevent CPF induced neurotoxicity.